2019
DOI: 10.1038/s41586-019-1448-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep roots for mid-ocean-ridge volcanoes revealed by plagioclase-hosted melt inclusions

Abstract: The global mid-ocean ridge system is the most significant magmatic system on our planet and is the site of 75% of Earth volcanism 1. The vertical extent of mid-ocean ridge magmatic systems has been considered to be restricted: even at the ultraslowspreading Gakkel Ridge, where the lithosphere is thickest, crystallisation depths of magmas feeding eruptions are thought to be <9 km 2. These depths have been determined using the volatile contents of melt inclusions, which are small volumes of magma that become tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 41 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Unfortunately, the vast majority of published volatile contents in melt inclusions globally, and at Kı̄lauea, only measured CO 2 in the glass phase, using techniques such as secondary‐ion mass spectrometry (SIMS), or Fourier‐transform infrared spectroscopy (FTIR; Bennett et al., 2019; Ruth et al., 2018; Sides, Edmonds, Maclennan, Houghton et al., 2014; Sides, Edmonds, Maclennan, Swanson et al., 2014). Given that recent work has shown that ∼40%–90% of the total CO 2 budget of melt inclusions may be held within the vapor bubble (Hartley et al., 2014; Moore et al., 2015; Rasmussen et al., 2020; Wallace et al., 2015), entrapment pressures from studies neglecting vapor bubble carbon must be viewed as minimum estimates (Anderson & Brown, 1993; Ruth et al., 2018).…”
Section: Melt Inclusion Entrapment Pressuresmentioning
confidence: 99%
“…Unfortunately, the vast majority of published volatile contents in melt inclusions globally, and at Kı̄lauea, only measured CO 2 in the glass phase, using techniques such as secondary‐ion mass spectrometry (SIMS), or Fourier‐transform infrared spectroscopy (FTIR; Bennett et al., 2019; Ruth et al., 2018; Sides, Edmonds, Maclennan, Houghton et al., 2014; Sides, Edmonds, Maclennan, Swanson et al., 2014). Given that recent work has shown that ∼40%–90% of the total CO 2 budget of melt inclusions may be held within the vapor bubble (Hartley et al., 2014; Moore et al., 2015; Rasmussen et al., 2020; Wallace et al., 2015), entrapment pressures from studies neglecting vapor bubble carbon must be viewed as minimum estimates (Anderson & Brown, 1993; Ruth et al., 2018).…”
Section: Melt Inclusion Entrapment Pressuresmentioning
confidence: 99%
“…Unfortunately, the vast majority of published volatile contents in melt inclusions globally, and at Kīlauea, only measured CO 2 in the glass phase, using techniques such as secondary-ion mass spectrometry (SIMS), or Fourier transform infrared spectroscopy (FTIR;Bennett et al, 2019;Ruth et al, 2018;. Given that recent work has shown that ∼40-90% of the total CO 2 budget of melt inclusions may be held within the vapor bubble (Hartley et al, 2014;Wallace et al, 2015;Moore et al, 2015;Rasmussen et al, 2020), entrapment pressures from studies neglecting vapor bubble carbon must be viewed as minimum estimates (Anderson & Brown, 1993;Ruth et al, 2018).…”
Section: The Importance Of Vapor Bubblesmentioning
confidence: 99%
“…Most of this heterogeneity can be linked to uneven distribution of melt generation within the mantle below the ridge axis (e.g., Tucholke and Lin, 1994;Dunn et al, 2005;Rubin and Sinton, 2007;Dunn, 2015 and references therein). Uneven melt supply results in the formation of intermittent and discontinuous magma reservoirs within the crust (e.g., Dick et al, 2003;Carbotte et al, 2015), contrasted reservoir geometry (axial magma chamber or sill intrusions; Jian et al, 2016;Canales et al, 2017), and variable depth of melt emplacement which can range between 2 and 16 km depth below seafloor (Dunn et al, 2005;Singh et al, 2006;Canales et al, 2017;Bennett et al, 2019). The common thread running through all processes that potentially govern magma accretion at spreading ridges is the importance of melt migration mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%